Evaluation of silver bio-functionality in a multicellular in vitro model: towards reduced animal usage in implant-associated infection research - Cecotto, Leonardo; Stapels, Daphne A. C.; van Kessel, Kok P. M.; Croes, Michiel; Lourens, Zeldali; Vogely, H. Charles; van der Wal, Bart C. H.; van Strijp, Jos A. G.; Weinans, Harrie; Amin Yavari, Saber (Frontiers in Cellular and Infection Microbiology, 2023)
Despite the extensive use of silver ions or nanoparticles in research related to preventing implant-associated infections (IAI), their use in clinical practice has been debated. This is because the strong antibacterial properties of silver are counterbalanced by adverse effects on host cells. One of the reasons for this may be the lack of comprehensive in vitro models that are capable of analyzing host-bacteria and host-host interactions. In this study, we tested silver efficacy through multicellular in vitro models involving macrophages (immune system), mesenchymal stem cells (MSCs, bone cells), and S. aureus (pathogen). Our model showed to be capable of identifying each element of culture as well as tracking the intracellular survival of bacteria. Furthermore, the model enabled to find a therapeutic window for silver ions (AgNO3) and silver nanoparticles (AgNPs) where the viability of host cells was not compromised, and the antibacterial properties of silver were maintained. While AgNO3 between 0.00017 and 0.017 µg/mL retained antibacterial properties, host cell viability was not affected. The multicellular model, however, demonstrated that those concentrations had no effect on the survival of S. aureus, inside or outside host cells. Similarly, treatment with 20 nm AgNPs did not influence the phagocytic and killing capacity of macrophages or prevent S. aureus from invading MSCs. Moreover, exposure to 100 nm AgNPs elicited an inflammatory response by host cells as detected by the increased production of TNF- and IL-6. This was visible only when macrophages and MSCs were cultured together. Multicellular in vitro models such as the one used here that simulate complex in vivo scenarios can be used to screen other therapeutic compounds or antibacterial biomaterials without the need to use animals.